2019
DOI: 10.1101/836221
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Accelerating functional gene discovery in osteoarthritis

Abstract: Osteoarthritis causes debilitating pain and disability, resulting in a huge socioeconomic burden, yet no drugs are available that prevent disease onset or progression. Here, we develop, validate and use rapid-throughput imaging techniques to identify abnormal joint phenotypes in unselected mutant mice generated by the International Knockout Mouse Consortium. We identify 14 genes with functional involvement in osteoarthritis pathogenesis, including the homeobox gene Pitx1, and functionally characterize 6 candid… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 102 publications
1
7
0
Order By: Relevance
“…A complementary approach to such in vitro functional studies is the investigation of risk alleles in mice. This has so far proven particularly insightful for the OA risk that maps to the GDF5 locus 41 and similar reports are appearing in the literature 88 . A recent database of genes associated with OA in animal models can complement these investigations 89 .…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…A complementary approach to such in vitro functional studies is the investigation of risk alleles in mice. This has so far proven particularly insightful for the OA risk that maps to the GDF5 locus 41 and similar reports are appearing in the literature 88 . A recent database of genes associated with OA in animal models can complement these investigations 89 .…”
Section: Discussionsupporting
confidence: 53%
“…A recent database of genes associated with OA in animal models can complement these investigations 89 . The degree to which the functional characterization of OA GWAS signals will benefit from animal models is open to debate, but clearly there are grounds for optimism 88,90 .…”
Section: Discussionmentioning
confidence: 99%
“…Luciferase reporter assays in these cells for rs6060369 found that the risk allele ''T'' drove reduced expression (Figure 6C, p = 0.000044; Fisher-combined p = 8.79EÀ09). We computationally predicted that Pituitary homeobox 1 (PITX1), a major TF in knee formation (Nemec et al, 2017) and OA factor (Butterfield et al, 2019;Picard et al, 2007), binds to this variant position. Using ChIP on T/C-28a2 cells (Figure 6D), E15.5 distal femur and proximal tibia cartilage, and PITX1 ChIPseq data (Figure 6E), we validated PITX1 binding at this position, indicating that it likely mediates the cis-acting effects of rs6060369 in R4 on GDF5 expression.…”
Section: Functional Interrogation Of An Oa Risk Locusmentioning
confidence: 99%
“…Studies from April 12,020 to April 30 2021 performing functional analysis of genetic variants for OA risk are summarized above With the intention of improving functional gene discovery in OA, Butterfield et al developed a three-mode imaging pipeline to comprehensively phenotype the mouse knee joint and its diseaserelated changes 27 . Iodine-contrast-enhancer (ICE) mCT determines several cartilage and bone volume, thickness and density characteristics, joint surface replication (JSR) quantifies cartilage surface damage, and subchondral bone X-ray microradiography (scXRM) determines mineral density.…”
Section: Osteoarthritis and Cartilagementioning
confidence: 99%